Probation as social work - Canton, Rob (Probation journal, 2024)
In England and Wales probation was regarded as social work for most of the twentieth century, but some thirty years ago the government rejected this conception. In the context of continuing deliberations about the purpose and character of probation, it is timely to revisit its relationship to social work. It is argued that a principal reason for the politically motivated repudiation of social work was its associations with care, but this rested on confusion about care and a comparable misunderstanding of the concept of control. Appreciation of social context is argued to be fundamental to the work of probation. Social capital is no less important than human capital in achieving desistance. The skills and values of social work continue to inform probation because they match up to the demands of the job. Reaffirming connections between the professions would enhance the policy and practices of both.